Inflexible Repositioning: Commitment in Competition and Uncertainty - Cong, Jiajia; Zhou, Wen (Management Science, 2020)
We study the value of commitment in a business environment that is both competitive and uncertain, in which two firms face stochastic demands and compete in positioning and repositioning. If the future demand tends to disperse or the demand uncertainty is sufficiently large, one firm chooses rigidity (i.e., commits not to change its positions), and the other chooses flexibility (i.e., to reposition freely). We find that a firm’s rigidity can benefit not only itself, but also its flexible rival. When uncertainty is larger, rigidity becomes more valuable relative to flexibility. These results arise because the asymmetric equilibrium generates two collective gains in addition to the usual individual gain (in terms of competitive advantages) accrued to the committing firm. A firm’s rigid repositioning can soften competition and generate a commitment value, and the other firm’s flexible repositioning generates an option value. Both values then spill over to competitors within the ecosystem. These results suggest that, when firms compete under uncertainty, commitment and options are valuable not only for the party that is making the choice, but also for all competing parties collectively. Commitment value and option value do not have to be mutually exclusive; they can coexist and even strengthen each other through unilateral commitment, which achieves the best of both strategies. This paper was accepted by Juanjuan Zhang, marketing.